Cabbage Looper, Trichoplusia ni (Hübner) (Insecta: Lepidoptera: Noctuidae): EENY-116/IN273, 10/1`999 - Capinera, John L. (EDIS, 2002)
This document is EENY-116, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 1999. Reviewed May 2003. EENY-116/IN273: Cabbage Looper, Trichoplusia ni (Hübner) (Insecta: Lepidoptera: Noctuidae) (ufl.edu)